The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.nanolett.9b05342
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Directionality in Quantum Dot Shell Lasing Using Plasmonic Lattices

Abstract: We report how the direction of quantum dot (QD) lasing can be engineered by exploiting high-symmetry points in plasmonic nanoparticle (NP) lattices. The nanolaser architecture consists of CdSe–CdS core–shell QD layers conformally coated on two-dimensional square arrays of Ag NPs. Using waveguide-surface lattice resonances (W-SLRs) near the Δ point in the Brillouin zone as optical feedback, we achieved lasing from the gain in CdS shells at off-normal emission angles. Changing the periodicity of the plasmonic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 39 publications
0
69
0
Order By: Relevance
“…Low-symmetry lattice geometries with rhombohedral unit cells also exploited the spasing mechanism, where changing the pump polarization resulted in different populations of molecules within the same electromagnetic hotspots contributing to lasing action and at very different wavelengths. Closing the loop on the original spaser design, we found that colloidal semiconductor quantum dots combined with plasmonic nanoparticle lattices could produce lasing action with both radially and azimuthally polarized light and with an emission beam at any desired angle. , …”
Section: Spasersmentioning
confidence: 99%
“…Low-symmetry lattice geometries with rhombohedral unit cells also exploited the spasing mechanism, where changing the pump polarization resulted in different populations of molecules within the same electromagnetic hotspots contributing to lasing action and at very different wavelengths. Closing the loop on the original spaser design, we found that colloidal semiconductor quantum dots combined with plasmonic nanoparticle lattices could produce lasing action with both radially and azimuthally polarized light and with an emission beam at any desired angle. , …”
Section: Spasersmentioning
confidence: 99%
“…[60] More recently, plasmonic cavities and lasers based on an array of nanostructures have been demonstrated. [61][62][63][64] For example, plasmonic nanoparticle arrays achieved a 200-fold enhancement of the spontaneous emission rate because of their large local density of states. [61] The upconverting laser in the plasmonic nanoarray coated with lanthanide-based upconverting nanoparticles was operated to provide directional, stable, CW output at visible frequencies under near-infrared pumping.…”
Section: Plasmonic Lasersmentioning
confidence: 99%
“…Integrating gain media with nanoparticle lattices can result in nanoscale lasing, where the high local density of optical states at the band edges provides optical feedback and the corresponding in-plane wavevectors of the band-edge states determine the emission angles. Lasing action can be used as an effective diagnostic tool to visualize the high-symmetry points of plasmonic lattices. …”
mentioning
confidence: 99%